HIGH SCHOOL STUDENT’S PERCEPTION OF A CAKE ENGLISH APPS TO IMPROVE SPEAKING SKILL - Annisa Marwati; Fitri Andini; Maman Suryaman (IKIP Siliwangi, 2022)
The focus of this research was to explore the students' perceptions about using the Cake English Apps to improve their speaking abilities. This study involved 14 students from class XI at SMK Giri Taruna Bogor. The qualitative descriptive method was used by the researchers in this study. Information was collected using questionnaires and interviews. The majority of the students, according to the research's findings, said that Cake English Apps gave more opportunities to practice their speaking abilities; they are interested in enhancing their speaking skills with the Cake English Apps, they can use the Cake English Apps to practice speaking as much as they like, and they like to choose the speaking-related content to practice their speaking skills. Four students walk in to be interviewed about using the Cake English Apps to improve their speaking skills; the majority of them are familiar with several of the features of the Cake Apps and understand how to use them. Finally, they will recommend the app to other students to help them improve their speaking skills. Keywords: Cake English Apps, Speaking Ability, Perception